Coumarins during Pregnancy: Long-term Effects on Growth and Development of School-age Children - Wesseling, J.; Driel, D. Van; Heymans, H. S. A.; Rosendaal, F. R.; Geven-Boere, L. M.; Smrkovsky, M.; Touwen, B. C. L.; Sauer, P. J. J.; Veer, E.Van der (Thrombosis and Haemostasis, 2001)
Anticoagulation during pregnancy is complicated because of potential risks for mother and foetus. Unfractionated or low-molecular-weight heparin is used for most anticoagulant indications. Its efficacy, however, in pregnant women with prosthetic heart valves is questioned, therefore coumarins are preferred for this indication.We studied long-term effects of prenatal coumarin-exposure on growth and on neurological, behavioural and cognitive development in 274 school-age children in comparison with 231 age-matched non-exposed controls. No major abnormalities were found. The exposed children had an increased risk for minor neurological dysfunction and for a low intelligence quotient (IQ below 80). The risk for a combination of two or more (minor) abnormalities was higher for the exposed children, RR = 7.6. We conclude that prenatal exposure to coumarins is associated with an increased risk for disturbances in development in school-age children. However, for the vast majority of children there is no clinical significant effect on growth and long-term development.
Keywords: Anticoagulants; long-term effect; growth; behaviour; neurological development; intelligence